Vegetable grafting: Principles and practices. - Colla, Giuseppe; Pérez-Alfocea, Francisco; Schwarz, Dietmar (CABI, 2017)
Although the benefits of using grafted transplants are now fully recognized worldwide, the need to enlighten the scientific basis of rootstock-scion interactions under variable environmental pressures remains vital for extracting grafting-mediated crop improvement. This has prompted the COST (European Cooperation in Science and Technology) Action FA1204 entitled 'Vegetable grafting to improve yield and fruit quality under biotic and abiotic stress conditions' aimed at systematizing research findings. The COST action allowed the development of a multidisciplinary network of partners targeting the root system and employing rootstock breeding to unravel the mechanisms behind rootstock-mediated crop improvement: the enhancement of productivity and fruit quality, and the sustainability of vegetable crops under multiple and combined stresses. The current book is the major output of the COST Action and contains nine chapters drawing on the 2012-16 activities of four Working Groups (WGs) dealing with 'Genetic resources and rootstock breeding' (WG1), 'Rootstock-scion interactions and graft compatibility' (WG2), 'Rootstock-mediated resistance to biotic and abiotic stresses' (WG3) and 'Rootstock-mediated improvement of fruit quality' (WG4). While recent advances of scientific knowledge constitute the core of this COST book, valuable practical information is also provided on rootstock-scion combinations, on applicable grafting methods, on the establishment of grafted transplants and on recommendations for the use of grafted plants as an effective tool for sustainable vegetable production. This book is compiled as a collection of scientific information and as a practical tool aimed at both the people involved in the commercial production and cultivation of grafted plants, as well as researchers interested in an understanding of the science and technology behind a grafted plant.